ANALISIS BUSINESS INTELEGENSI PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN ALGORITMA REGRESI LINIER - Sitorus, Zulham; Syahputri, Maulisa; Nainggolan, Andreas Ghanneson; Sibarani, Dina Marsauli; Nahampun, Natalia; Putra, Khairil (Politeknik Bisnis Indonesia, 2024)
Prima Indonesia University is a leading private university in the city of Medan, operating in the education sector which applies Business Intelligence to its management system. This research was conducted using the Linear Regression Algorithm to measure the influence of Emotional Intelligence on Employee Performance at Prima Indonesia University, totaling 212 data. The data used in this research is employee performance history data for the last 5 years. Next, the Linear Regression Algorithm is applied to the processed dataset. The research results will later show that the Linear Regression Algorithm is able to produce quite accurate measurements. The results of this research can show how much emotional intelligence influences an employee's performance. Thus, the Linear Regression Algorithm can be a solution in evaluating the influence of Emotional Intelligence on Employee Performance, and can provide long-term recommendations for increasing the productivity of Employee Performance at Prima Indonesia University.